Features of temperature regulation as a task for assortment of bread baking - Ladanyuk, Anatoly; Ivashchuk, Vyacheslav; Echkalov, Dmitriy (My University, 2014)
Factors which have strongest effect on baking temperature in oven with circulation of heating gas have been found. Estimate of moisture which is obtained from vapor of dough surface and spreading via recycling composite of heating gas. Different parts of mathematical equation dependent on the condition control point and environment in baking zone. So our recommendation may help the engineer who will be developing a system of controlling baking, guiding the way that heat flow will be adequate to determine the order of baking zones for ordered assortment.
Keywords: хліб; випічка; тісто; управління; хлеб; выпечка; тесто; управление; bread; baking; dough; control; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка